Image and Communication: the Weight of Photography in International Digital Journalism - Fondevila Gascón, Joan Francesc; Cardona Pérez, Carlos; Santana López, Eva; Rom Rodríguez, Josep; López Crespo, Javier; Mir Bernal, Pedro (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2016)
Photography is one of the singular indicators of digital journalism. Among its exponents (text, photography, video, sound or graphics), photography metamorphoses into the virtual environment. Through an empirical analysis, we compare the reference newspapers from four countries of global relevance: Germany, USA, Japan and the UK. The reference digital versions of the most read newspapers in these countries are Spiegel Online, The New York Times, The Japan Times, and The Times. The items analyzed in this work are all the text units published at the home page, including the number of existing photographs in total content units and the number of different types of pictures, classified in ten different parameters: photo-news, illustrative, new, resource, black and white, color, large format, small format, edited, unedited. This work confirms that photojournalism is losing its relevance at the multimedia area and that photography gives way to the purely illustrative side...